Environmental Awareness, Government Promotion, Perceived Price Value, Lifestyle, dan Perceived Risk Terhadap Minat Beli Kendaraan Listrik. - Faujiyah, Firdhani; Rahmawati, Anisa; Yuniarti, Trisna (JURNAL ILMIAH MANAJEMEN & BISNIS, 2025)
Purpose – This study aims to examine the factors influencing consumer purchase intention toward electric vehicle products in the Greater Jakarta Area (Jabodetabek).  Methodology – Through purposive sampling of motor vehicle users in the Jabodetabek area, a total of 1780 questionnaire responses were collected. Then the data were analysed using the Sequential Equation Modelling (SEM) method - PLS.Findings – Based on the analysis's results, lifestyle is the most influential factor affecting consumers' purchase intention of electric vehicles, compared to other factors studied. In contrast, environmental awareness does not significantly influence consumers’ intention to purchase electric vehicles.Originality/Novelty – This study offers a new perspective on how environmental awareness, government promotion, perceived price value, lifestyle, and perceived risk affect purchase intention toward electric vehicles in the Jabodetabek area. Consequently, it provides insights for developing more effective marketing strategies and public policies to reach potential consumers.Implications – Despite adequate infrastructure, along with supportive government policies and subsidies aimed at promoting the adoption of electric vehicles to reduce carbon emissions in the Jabodetabek area, environmental awareness alone does not significantly drive consumer interest. Instead, lifestyle emerges as the most influential factor in shaping consumer purchase intention. These findings suggest that stakeholders should consider lifestyle-oriented strategies to enhance the effectiveness of marketing policies and promote electric vehicle adoption as part of the border to reduce carbon emissions